Wyroki Trybunału Konstytucyjnego o odżyciu przepisów - Tkaczyk, Edyta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article is concerned with revival of regulations in Polish and Austrian law. The subject of the article is a detailed matter referring to the so-called verdicts on revival of validity of previously applicable regulations. The point of departure is the fact that if the act is repealed by way of CT verdict due to its inconsistency with the constitution, pursuant to the art. 140 para. 6 of the Austrian Federal Constitution, on the revoking day the regulations of the act previously repealed by way of the act acknowledged by CT as inconsistent with the Constitution shall become effective again. The influence of the above on the legal system is considerable and questionable. In Poland this issue is new and has not been finally settled.
Keywords: Constitutional Tribunal; the Austrian Federal Constitution; effect of regulations revival verdict; revival of regulations